Emergency department visits in Italy: 2017-2023 trends, decline and recovery - Camilla Mattiuzzi; Giuseppe Lippi; Ciro Paolillo (Emergency Care Journal)
This study analyzes the trend of Emergency Department (ED) visits in Italy between 2017-2023 using data of Italian National Institute for Statistics (ISTAT). We found a fluctuating trend, with ED visits peaking in 2019, followed by a sharp decline in 2020 and 2021, and partial recovery in 2022 and 2023. In 2023, the ED visit rate reached 58.5 per 1,000 population, marking a 25.6% reduction compared to 2019, but with a 4.7% increase from 2022. The decline during the pandemic affected all age groups, with the 0–5 years category exhibiting an anomalous surge in 2023, recording the second-highest ED visit rate after that of older people. ED visits generally increased with age, but older adults (>75 years) continued to access EDs at lower rates post-pandemic. Sex-stratified trends mirrored overall patterns, though the decline from 2019 to 2023 was more pronounced in females than in males. The trends observed across the macro-regions closely mirror national data, with the most significant decline occurring in South and Islands regions. These findings indicate that the pandemic has resulted in enduring changes in both economic and healthcare-seeking behaviors, supported by a range of potential contributing factors, the impact of which remains challenging.